Functional Mapping of AGO-Associated Zika Virus-Derived Small Interfering RNAs in Neural Stem Cells - Zeng, Jianxiong; Luo, Zhifei; Dong, Shupeng; Xie, Xiaochun; Liang, Xinyan; Yan, Youzhen; Liang, Qiming; Zhao, Zhen (Frontiers in Cellular and Infection Microbiology, 2021)
Viral interfering RNA (viRNA) has been identified from several viral genomes via directly deep RNA sequencing of the virus-infected cells, including zika virus (ZIKV). Once produced by endoribonuclease Dicer, viRNAs, similar to microRNAs, are loaded onto Argonaute (AGO) family proteins of the RNA-induced silencing complexes (RISCs) to pair with their RNA targets and then initiate cleavage of the target genes. However, identities of functional ZIKV viRNAs and their viral RNA targets remain largely unknown. By combining AGO-associated RNA sequencing, deep sequencing analysis in ZIKV-infected neural stem cells (NSCs), and miRanda target scanning, we have defined 29 ZIKV derived viRNA profiles in NSCs, and established the complex interaction networks between the viRNAs and their viral targets. Our recent study has shown that ZIKV capsid protein interacted with Dicer and antagonized its endoribonuclease activity depending on its histidine (H) at the 41st amino acid. Accordingly, the rescued ZIKV-H41R mutant virus, compared to wild-type ZIKV, no longer suppressed Dicer enzymatic activity and consequently failed to inhibit miRNA biogenesis in NSCs. As a result, much higher levels of viRNAs generated from the ZIKV-H41R virus-infected NSCs, suggesting Dicer-dependent viRNA production. Knockdown of individual RNAi machinery in ZIKV-infected NSCs suggests that viRNA is a limiting factor of ZIKV infection in NSCs. The mapping of viRNAs to their RNA targets is paving a way to further investigate how viRNAs play the role in anti-viral mechanisms or even other unknown biological functions.